Comparison of Neoadjuvant Immunotherapy Plus Chemotherapy versus Neoadjuvant Chemoradiotherapy for Patients with Esophageal Squamous Cell Carcinoma: A Propensity Score Matching Study - Zhao J; Hao S; Tian J; Li Y; Han D (Journal of Inflammation Research, 2023)
Junfeng Zhao,1,2,* Shaoyu Hao,3,4,* Jing Tian,5 Ying Li,6 Dan Han1,2 1Department of Radiation Oncology, Shandong University Cancer Center, Jinan, Shandong, People’s Republic of China; 2Department of Radiation Oncology, Shandong Cancer Hospital and Institute, Shandong First Medical University, and Shandong Academy of Medical Sciences, Jinan, Shandong, People’s Republic of China; 3Department of Thoracic Surgery, Shandong University Cancer Center, Jinan, Shandong, People’s Republic of China; 4Department of Thoracic Surgery, Shandong Cancer Hospital and Institute, Shandong First Medical University, and Shandong Academy of Medical Sciences, Jinan, Shandong, People’s Republic of China; 5Department of Radiation Oncology, Jinan Zhangqiu District People’s Hospital, Jinan, Shandong, People’s Republic of China; 6Department of Medical Oncology, Shandong Cancer Hospital and Institute, Shandong First Medical University, and Shandong Academy of Medical Sciences, Jinan, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dan Han, Department of Radiation Oncology, Shandong University Cancer Center, Shandong Cancer Hospital and Institute, Shandong First Medical University, and Shandong Academy of Medical Sciences, Jinan, Shandong, People’s Republic of China, Tel +86-17862893373, Email echohandan@163.comPurpose: This study compares the efficacy and safety of neoadjuvant immunotherapy combined with chemotherapy (NICT) and neoadjuvant chemoradiotherapy (NCRT) combined with radical esophagectomy in patients with resectable, locally advanced esophageal squamous cell cancer (ESCC).Patients and Methods: Patients with locally advanced ESCC treated with NICT or NCRT combined with esophagectomy between March 2016 and May 2022 were retrospectively analyzed and propensity score matched (PSM) in a 1:2 ratio to balance potential bias.Results: After PSM, 110 patients who received NCRT and 55 patients who received NICT were selected for the final analysis. The probability of tumor regression grade 0 and the rate of pathological complete remission (pCR) were significantly higher in the NCRT group than in the NICT group (57.3% vs 32.7%, P=0.003 and 48.2% vs 29.1%, P=0.030, respectively). The incidence of postoperative complications in the NCRT group was not significantly different from that in the NICT group (P=0.082). Patients in the NCRT group had significantly better disease-free survival (DFS) and overall survival (OS) than those in the NICT group (12-month DFS rate: 94.3% vs 81.8%, P=0.006; 12-month OS rate: 100.0% vs 95.4%, P=0.032). However, the results of the 24-month follow-up showed that there was also a statistically significant difference in DFS between the two groups. Patients with postoperative pCR had a longer DFS (P< 0.001).Conclusion: Short-term follow-up results show that NCRT has a significantly better pathologic response and prognosis than NICT in the treatment of patients with locally advanced ESCC. NCRT and NICT have similar safety profiles.Keywords: esophageal squamous cell carcinoma, neoadjuvant, chemoradiotherapy, immunotherapy, immune checkpoint inhibitor, esophagectomy